(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: Hepatitis C is one of the most common causes of liver disease worldwide. Health impacts of hepatitis C are not limited to physical morbidity but include psychosocial dimensions such as quality of life (QOL), depression, anxiety, and stigmatization. In Malaysia, modifiable factors that can improve QOL among hepatitis C patients have not been adequately studied. Resilience – defined as the capacity to endure hardships and rebound from life adversities – is associated with mental health and well-being. Our study aims to test the association between resilience and QOL among hepatitis C patients. Methods: Employing a cross-sectional design, 195 hepatitis C patients who attended Hospital Tengku Ampuan Afzan (HTAA) – the main public tertiary hospital in Pahang – were recruited through convenience sampling. Resilience was assessed using the Connor-Davidson resilience scale while Health-Related Quality of Life (HRQOL) was measured by 36-item short-form survey (SF-36v2). Multiple linear regression was run to determine the association between resilience and HRQOL. Results: We found significant associations between resilience and the physical (b=0.35; 95% CI: 0.11, 0.30; p<0.001) and mental dimension of HRQOL (b=0.47; 95% CI: 0.21, 0.42; p<0.001). Patients with higher resilience scores were more likely to have better HRQOL compared to those less resilient. Conclusion: Resilience may be a protective factor in the disease trajectory of hepatitis C in terms of QOL. Health care providers should incorporate resilience into the management of hepatitis patients, through a multidisciplinary approach. Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 165-170